Analysis of the representations of pain in healthcare professionals from a IV level hospital in Bogotá, Colombia (2018)
Introduction: Pain is a manifestation difficult to describe objectively. Understanding and managing pain by the clinical staff is not just based on scientific concepts, but on representations affected by subjectivity. Objectives: To describe the social representations of pain in the discourse and behavior of the healthcare staff in a medical hospital in Bogotá. Materials and methods: A qualitative, descriptive, cross-sectional trial was conducted using 2 data collection techniques: (i) semi-structured interviews (n=45), including the natural semantics networks technique; (ii) a non-participant observation with a field diary. Results: In the natural semantic network, many descriptors mentioned by the participants (n=88) were identified. The terms referring to the emotional experience were mentioned more often, followed by terms referring to medical care. The field observation identifies a broad diversity in the way pain is understood, marked by a trend to underestimate the subjective aspects of pain. Conclusions: The data, which may be representative of similar institutions in the Colombian and Latin American context, illustrate that there has been a growing interest in approaching pain as a priority in the comprehensive management of the patient. However, strategies are yet to bepromoted that result in a more assertive communication, and an identification and legitimation of emotions and subjective suffering of the patient in pain. Copyright © 2018 Sociedad Colombiana de Anestesiología y Reanimación (S.C.A.R.E.).